MINAT BELI ANGGOTA KOPERASI UKHUWAH MUAMALAH ISLAMIYAH DI UMI MART KELAPA DUA KABUPATEN TANGERANG - Sunardi Sunardi; Martavevi Azwar; Anika Sari (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2019)
This study aims to determine the factors of influencing Ukhuwah Muamalah Islamiyah cooperative members’purchasing intentionat UMI Mart. The study was conducted by distributing questionnaires to 60 members of the Ukhuwah Muamalah Islamiyah Cooperative as respondents in this study. The method used in this research is quantitative descriptive with statistical testing measurement by multiple linear regression models consisting of dependent variables, namely the purchasing intention of members’ of the Cooperative Ukhuwah Muamalah Islamiyah.Factors used as independent variables in this study are product (X1), promotion (X2), price (X3) and Location (X4). The finding of this study indicates that product factors (X1), promotion (X2), price (X3) and location (X4) simultaneously have a significant effect on buying interest of members of the Ukhuwah Muamalah Islamiyah Cooperative, while partially product variables (X1), promotion (X2), price (X3) and Location (X4) have positive and significant effect on buying interest variable (Y).